2009
DOI: 10.3350/kjhep.2009.15.2.193
|View full text |Cite
|
Sign up to set email alerts
|

A case of hypervascular hyperplastic nodules mimicking hepatocellular carcinoma in alcoholic liver cirrhosis

Abstract: Benign hypervascular hyperplastic nodules (HHN) in liver cirrhosis are very rare. It is important to distinguish between regenerative nodules (hyperplastic nodules) and tumorous nodules (dysplastic or neoplastic nodules) in hepatocellular nodular lesions. The differential diagnosis between HHN and hepatocellular carcinoma on the basis of radiologic imaging is often difficult, and is clinically important when determining the therapeutic plan. Therefore, histological confirmation by needle biopsy sampling of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This biochemical change is a diagnostic marker for alcoholic fatty liver disease in the medical population [ 57 ]. As fibrosis progresses in the liver, ALT activity commonly decreases and AST to ALT gradually increases due to ALT production decrease [ 58 ]. We observed fibrosis in the liver at 3, 6, and 9 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This biochemical change is a diagnostic marker for alcoholic fatty liver disease in the medical population [ 57 ]. As fibrosis progresses in the liver, ALT activity commonly decreases and AST to ALT gradually increases due to ALT production decrease [ 58 ]. We observed fibrosis in the liver at 3, 6, and 9 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al 3 reported a case of HHN in alcoholic liver cirrhosis, in which the nodules showed no change in size and number after four months from the initial diagnosis. In the case reported herein, 3D CT was performed after six months, and the follow-up 3D CT showed that the nodules had the same sizes and numbers.…”
Section: Introductionmentioning
confidence: 99%
“…In South Korea, liver cancer ranks second in terms of crude death rate, imposing the highest economic burden among all cancer types. 1 2 3 The Korean Liver Cancer Association (KLCA), formerly known as the Korean Liver Cancer Study Group (KLCSG), and the National Cancer Center (NCC) Korea initially issued practice guidelines for managing hepatocellular carcinoma (HCC) in 2003, 4 subsequently revising them in 2009, 5 2014, 6 and 2018. 7 Over time, advancements in research and therapies have accumulated, prompting a recent revision of the guidelines to incorporate the latest research findings, novel therapies, and expert opinions.…”
mentioning
confidence: 99%